(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In today’s globalized world, communicative competence in English is a critical skill for students preparing to enter professional fields. This paper investigates the role of career orientation in enhancing communicative competence in English language teaching. It explores how incorporating career-related contexts, tasks, and vocabulary into English lessons improves motivation, relevance, and practical language skills. Through a review of recent literature, classroom-based observations, and pedagogical examples, the study demonstrates that aligning English language instruction with students’ future professions significantly contributes to language acquisition and real-world readiness. The findings offer practical insights for curriculum developers and educators aiming to equip students with essential communicative skills tailored to their professional trajectories.